Method for sintering titanium alloy by ultraviolet light assisted activation and its products and applications
Through ultraviolet assisted activation sintering technology, the problem of difficulty in preparing large-scale structural parts in the existing titanium alloy preparation technology is solved, and the preparation of high-performance titanium alloys is realized, with low cost, high efficiency and safety.
Patent Information
- Application Number
- CN202310128029.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-14
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-02-14
Smart Images

Figure CN116144959B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of titanium alloy activation sintering preparation, and more specifically, relates to a method for ultraviolet light assisted activation sintering of high-performance titanium alloy, and a product and application thereof. Background Art
[0002] Titanium and titanium alloys have the characteristics of high specific strength, good corrosion resistance, and excellent biocompatibility, and have broad application prospects in aerospace, marine engineering, petrochemical, biomedicine and other fields. However, the traditional titanium alloy preparation method has a long process and high energy consumption, and the titanium element is highly active and difficult to process, resulting in high processing costs and high prices for high-performance titanium alloys, which seriously restricts its development and application process. The titanium alloy powder metallurgy preparation process uses titanium alloy powder as raw material, which is pressed, formed and sintered.
[0003] At present, the alloying temperature of powder metallurgy titanium alloy is usually higher than 1200℃. During high temperature sintering, cracking, coarse grains, segregation of structure and other phenomena are prone to occur. Conventional pressureless sintering is difficult to provide sufficient driving force, which easily leads to low sintering density of titanium alloy parts, usually only 95%. The large number of pores seriously affects the performance of the material. In order to obtain titanium alloy parts with excellent performance, the titanium alloy powder must be surface activated to purify the grain boundary, improve the organization and maintain the fine grain structure, so as to improve its processing performance and mechanical properties, so as to meet the requirements of practical applications.
[0004] The advantage of using titanium hydride powder as raw material to directly form and sinter titanium and titanium alloys in a one-step process is that the hydrogen in titanium hydride can weaken the titanium-titanium bond and increase the atomic diffusion rate, thereby improving the sintering activity of titanium and increasing the density of the sintered body. However, due to the brittleness of titanium hydride powder, it is difficult to prepare large-sized titanium alloy structural parts (no more than 1kg), which seriously limits the application of this process.
[0005] The field-assisted activated sintering technology can also be used to achieve low-temperature rapid densification of titanium alloy powder. This process applies a pulse current in the initial stage of sintering to generate electric sparks or plasma arcs between powder particles, removing the oxide film and impurities on the powder surface and densifying the powder. However, this method has high requirements on equipment conditions and cannot be used to prepare large-scale structural parts.
[0006] It can be seen that the existing titanium alloy preparation technology has the technical problem of being difficult to prepare large-scale structural parts while ensuring density and mechanical properties. Summary of the invention
[0007] In response to the above defects or improvement needs of the prior art, the present invention provides a method for sintering high-performance titanium alloy by ultraviolet light-assisted activation, thereby solving the technical problem that the existing titanium alloy preparation technology is difficult to prepare large-scale structural parts while ensuring density and mechanical properties.
[0008] To achieve the above object, according to one aspect of the present invention, a method for sintering a high-performance titanium alloy by ultraviolet light assisted activation is provided, comprising the following steps:
[0009] (1) mixing the hydrogenated dehydrogenated titanium powder and the intermediate alloy powder required for preparing the target titanium alloy according to the target titanium alloy component ratio to obtain an original powder;
[0010] (2) Using ultraviolet light to irradiate the original powder from different angles to perform activation treatment to obtain activated powder, pressing the activated powder into a billet, and sintering the billet to obtain a high-performance titanium alloy.
[0011] Furthermore, the activation treatment is achieved by:
[0012] The original powder is placed in a light-transmitting device, and while the light-transmitting device is rotated, ultraviolet light is used to irradiate the original powder from the outside of the light-transmitting device to perform activation treatment.
[0013] Furthermore, the activation treatment is achieved by:
[0014] After the original powder is placed in the light-transmitting device, the light-transmitting device is placed in a box with an ultraviolet light source. While the light-transmitting device is rotated, the ultraviolet light in the box irradiates the original powder from different angles to perform activation treatment.
[0015] Furthermore, the light-transmitting device is a sealed container. Before the original powder is irradiated with ultraviolet light, the original powder is placed in the light-transmitting device, which is first evacuated and then protected by an inert gas.
[0016] The rotation time of the light-transmitting device and the ultraviolet light irradiation time can be the same or different, but the rotation time of the light-transmitting device and the ultraviolet light irradiation time can be the same, so that the powder can be fully irradiated while ensuring that the powder is fully mixed, so that the powder can be evenly activated.
[0017] Furthermore, the distance between the ultraviolet light and the original powder is 1 cm-10 cm, the power of the ultraviolet light is 80W-300W, the irradiation time is 12h-24h, the sintering temperature is 900°C-1200°C, and the sintering time is 0.5h-3h.
[0018] Furthermore, the distance between the ultraviolet light and the original powder is 1 cm-3 cm, the power of the ultraviolet light is 200W-300W, the irradiation time is 20h-24h, the sintering temperature is 900°C-1000°C, and the sintering time is 0.5h-2h.
[0019] Furthermore, the distance between the ultraviolet light and the original powder is 1 cm-3 cm, the power of the ultraviolet light is 100W-200W, the irradiation time is 20h-24h, the sintering temperature is 950°C-1050°C, and the sintering time is 0.5h-2h.
[0020] Furthermore, the light-transmitting device is a quartz container with a thickness of 0.5 mm to 1.5 mm, and the particle size of the original powder is less than or equal to 150 μm. The shape of the light-transmitting device is cylindrical, elliptical or shuttle-shaped, and the volume of the original powder filled in the light-transmitting device is less than or equal to one-fourth of the volume of the light-transmitting device. When the cylindrical light-transmitting device is rotated, the powder is mixed most evenly.
[0021] Further, the target titanium alloy is TA2 or Ti80. The pressing method is die pressing or cold isostatic pressing. The inert gas is nitrogen, argon or helium.
[0022] According to another aspect of the present invention, a high-performance titanium alloy sintered by ultraviolet light assisted activation is provided. The high-performance titanium alloy is prepared by a method of sintering a high-performance titanium alloy by ultraviolet light assisted activation. The high-performance titanium alloy has a tensile strength greater than or equal to 600 MPa and a density greater than or equal to 98%.
[0023] According to another aspect of the present invention, an application of a high-performance titanium alloy sintered by ultraviolet light assisted activation is provided, wherein the high-performance titanium alloy is prepared by a method for sintering a high-performance titanium alloy by ultraviolet light assisted activation, and the high-performance titanium alloy is used to prepare a large-sized titanium alloy structural part with a mass greater than 1 kg.
[0024] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects compared with the prior art:
[0025] (1) The titanium alloy powder used in the present invention can effectively improve the diffusion rate and uniformity of alloy elements after ultraviolet light-assisted activation. Ultraviolet light irradiates the original powder from different angles for activation treatment, which reduces the sintering temperature of the titanium alloy to a certain extent, improves the sintering density, and improves the mechanical properties of the material, exploring low-cost, efficient, and safe synthesis routes and products for the future industrial production of titanium alloys. The present invention uses ultraviolet light to assist in the activation of titanium alloy powder. Ultraviolet light, as a common photochemical medium, is often used in modern industrial production processes due to its simplicity and ease of operation. It is convenient for large-scale processing of titanium alloy powder and provides low-cost active raw materials for the preparation of large-scale titanium alloy structural parts. In addition to solving the technical problem that it is difficult to prepare large-scale structural parts while ensuring density and mechanical properties in the existing titanium alloy preparation technology, the method of the present invention also produces other unexpected effects. For example, the ultraviolet light-assisted activation of titanium alloy powder used in the present invention has a certain cleaning effect, which is conducive to the decomposition of surface titanium dioxide and reduces the oxygen content in the titanium alloy powder, thereby preparing titanium alloy structural parts with less impurities and high quality. The present invention adopts ultraviolet light to assist in activating titanium alloy powder, which can not only stimulate active groups on the surface of metal powder to achieve in-situ modification of the material, but also can maintain the purity of the original powder without changing the chemical composition of the powder and reducing the contamination of foreign substances.
[0026] (2) The present invention places the original powder in a light-transmitting device, so that ultraviolet light can penetrate the device to irradiate the powder. The light-transmitting device rotates while the ultraviolet light is used to irradiate the original powder. In this way, the original powder can be evenly mixed when the device rotates. While the powder is evenly mixed, the ultraviolet light can irradiate the original powder from different angles to achieve powder activation. The light-transmitting device is placed in a box with an ultraviolet light source, so that the original powder can be fully irradiated by ultraviolet light at different angles.
[0027] (3) The light-transmitting device in the present invention is a sealed container. The original powder is placed in the light-transmitting device, which is first evacuated and then protected by an inert gas. This ensures that the original powder is not contaminated by other impurities during the activation process, thereby ensuring the activation effect.
[0028] (4) The distance between the ultraviolet light and the original powder is too far, which will affect the activation effect. The distance between the ultraviolet light and the original powder, the power of the ultraviolet light, and the irradiation time of the ultraviolet light have an impact on the subsequent sintering process. The closer the distance between the ultraviolet light and the original powder, the greater the power of the ultraviolet light, the longer the ultraviolet light irradiation time, the better the activation effect, the lower the sintering temperature, and the shorter the sintering time. When no ultraviolet light irradiation is performed, the sintering temperature is 1250°C and the sintering time is 4 hours. When ultraviolet light irradiation is performed, the sintering temperature is shortened by a maximum of 350°C and the sintering time is shortened by a maximum of 3.5 hours. This fully demonstrates that compared with the traditional method, the present invention can greatly reduce the sintering time and sintering temperature of titanium alloys, improve the density of the material, and significantly reduce the production cost. It has a strong prospect for industrial application.
[0029] (5) Ordinary glass has poor transmittance to ultraviolet light, which will affect the activation effect. Therefore, the present invention uses a quartz container, which can transmit ultraviolet light and improve the activation effect. The thickness of the quartz device is limited to ensure the activation effect. When the particle size of the original powder is greater than 150 μm, it will affect the sintering density and the material performance will be greatly reduced.
[0030] (6) The present invention has found through comparative tests that the titanium alloy obtained by ultraviolet light assisted activation sintering has better mechanical properties, the tensile strength of the titanium alloy is greater than or equal to 600MPa, and the density is greater than or equal to 98%. However, the titanium alloy obtained by direct sintering without ultraviolet light assisted activation has poor mechanical properties, the tensile strength is only 430Mpa, a large number of pores remain inside the material, and the density is less than 95%. The comparative experiment fully proves that the high-performance titanium alloy sintered by ultraviolet light assisted activation of the present invention has greatly improved the mechanical properties and density while reducing the sintering temperature and shortening the sintering time. At the same time, the comparative test also found an unexpected increase in elongation. The elongation of the high-performance titanium alloy sintered by ultraviolet light assisted activation reached 30%, while the elongation of the titanium alloy obtained by direct sintering without ultraviolet light assisted activation was 23%.
[0031] (7) The present invention has low requirements on equipment conditions. It only requires the combination of a light-transmitting device and an ultraviolet light source to produce high-activity sites in the metal powder, thereby preparing a high-performance titanium alloy. Therefore, the titanium alloy prepared by the present invention can be used to prepare large-sized titanium alloy structural parts with a mass greater than 1 kg, thereby achieving lightweight structural parts of products such as aviation, aerospace, military and civilian use. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is a schematic diagram of a titanium alloy powder activation device provided in an embodiment of the present invention;
[0033] Figure 2 is a SEM image of the ultraviolet-activated powder prepared in Example 1 of the present invention;
[0034] Figure 3 is a crystal phase diagram of the titanium alloy prepared in Example 1 of the present invention;
[0035] Figure 4 It is a comparison diagram of mechanical property curves of titanium alloys prepared in Example 1 of the present invention and in Comparative Example 1;
[0036] Figure 5 This is a SEM image of the powder prepared in Comparative Example 1 of the present invention without UV activation;
[0037] Figure 6 It is a crystal phase diagram of the titanium alloy prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0039] A method for sintering high-performance titanium alloy by ultraviolet light assisted activation comprises the following steps:
[0040] (1) mixing the hydrogenated dehydrogenated titanium powder and the intermediate alloy powder required for preparing the target titanium alloy according to the target titanium alloy component ratio to obtain an original powder;
[0041] (2) Using ultraviolet light to irradiate the original powder from different angles to perform activation treatment to obtain activated powder, pressing the activated powder into a billet, and sintering the billet to obtain a high-performance titanium alloy.
[0042] The original powder was placed in Figure 1 In the sealed quartz container shown, an inert gas is introduced for protection after evacuation, and while the quartz container is rotated, ultraviolet light is irradiated to the original powder for a certain period of time for activation treatment.
[0043] The method of the present invention based on ultraviolet light-assisted activation of titanium alloy powder can be applied to various materials, including but not limited to TA2 and Ti80.
[0044] The power of the ultraviolet light is 80 to 300 W, and the quartz container is rotated to mix the original titanium alloy powder evenly. The mixing time of the powder is the same as the illumination time, which is 12 to 24 hours.
[0045] The activated titanium alloy powder is pressed into a blank by die pressing, cold isostatic pressing, etc. Blanks of various shapes can be pressed as needed. Cold isostatic pressing is used for pressing, with a pressure of 220-280 MPa and a holding time of 5-20 min; die pressing is used for pressing, with a pressure of 350-600 MPa and a holding time of 1-5 min.
[0046] The sintering temperature is between 900-1200°C, and the holding time is 0.5-3h. The optimal sintering temperature and holding time depend on the ultraviolet irradiation time.
[0047] Based on the principle of powder metallurgy, the present invention adjusts the activation process of titanium alloy powder, develops a method for activating titanium alloy powder by ultraviolet light on the basis of the above-designed equipment, and prepares high-performance titanium alloy materials by pressing and sintering on this basis. The preparation method has low cost, simple process, and controllable impurity content, and significantly improves the sintering activity of the material without changing the chemical composition of the material. To a certain extent, the sintering temperature of the titanium alloy is reduced, and its sintering density is improved, so that titanium alloy parts with higher performance are obtained, and a low-cost, efficient and safe synthesis route and product are explored for the future industrial production of high-performance titanium alloys.
[0048] The following are examples and comparative examples:
[0049] Example 1
[0050] (1) The hydrogenated dehydrogenated titanium powder and the intermediate alloy powder required for preparing the target titanium alloy were mixed according to the target titanium alloy TA2 component ratio to obtain an original powder with an average particle size of 75 μm. The original powder was transferred to a sealed quartz container and evacuated to 10 -3 After 1000 Pa, argon gas was introduced for protection, and ultraviolet light was used to irradiate the original powder outside the light-transmitting device for activation treatment while rotating the light-transmitting device. The ultraviolet light power was 200 W and the ultraviolet light irradiation time was 24 h.
[0051] (2) The activated powder in step (2) is pressed into a cylindrical billet by cold isostatic pressing at a pressure of 250 MPa and a holding time of 10 min.
[0052] (3) The temperature is raised to 1100°C at a rate of 10°C / min and sintered for 3 h to obtain a high-performance titanium alloy material.
[0053] Comparative Example 1
[0054] (1) The hydrogenated dehydrogenated titanium powder and the intermediate alloy powder required for preparing the target titanium alloy are mixed according to the target titanium alloy TA2 component ratio to obtain an original powder with an average particle size of 75 μm. The original powder is pressed into a cylindrical billet by cold isostatic pressing at a pressure of 250 MPa and a holding time of 10 min.
[0055] (2) The temperature is raised to 1250°C at a rate of 10°C / min and sintered for 4 hours to obtain a high-performance titanium alloy material.
[0056] Example 2
[0057] (1) The hydrogenated dehydrogenated titanium powder and the intermediate alloy powder required for preparing the target titanium alloy were mixed according to the target titanium alloy TA2 component ratio to obtain an original powder with an average particle size of 75 μm. The original powder was transferred to a sealed quartz container and evacuated to 10 -3 After 1000 Pa, argon gas was introduced for protection, and the quartz container was placed in a box with an ultraviolet light source. While the light-transmitting device was rotated, the ultraviolet light in the box irradiated the original powder from different angles for activation treatment. The ultraviolet light power was 200 W and the ultraviolet light irradiation time was 24 h.
[0058] (2) The activated powder in step (2) is pressed into a cylindrical billet by cold isostatic pressing at a pressure of 250 MPa and a holding time of 10 min.
[0059] (3) The temperature is raised to 1000°C at a rate of 10°C / min and sintered for 3 h to obtain a high-performance titanium alloy material.
[0060] Example 3
[0061] (1) The hydrogenated dehydrogenated titanium powder and the intermediate alloy powder required for preparing the target titanium alloy are mixed according to the composition ratio of the target titanium alloy Ti80 to obtain an original powder with an average particle size of 85 μm. The original powder is transferred to a sealed quartz container and evacuated to 10 -3 After Pa, argon gas was introduced for protection, and the original powder was irradiated with ultraviolet light outside the light-transmitting device for activation treatment while the light-transmitting device was rotated. The ultraviolet light power was 80W, the ultraviolet light irradiation time was 12h, the distance between the ultraviolet light and the original powder was 1cm, and the container thickness was 1cm;
[0062] (3) The activated powder in step (2) is pressed into a cylindrical blank by molding at a pressure of 600 MPa and the pressure is maintained for 2 minutes.
[0063] (4) The temperature is raised to 1200°C at a rate of 10°C / min and sintered for 2 h to obtain a titanium alloy material.
[0064] Example 4
[0065] (1) The hydrogenated dehydrogenated titanium powder and the intermediate alloy powder required for preparing the target titanium alloy are mixed according to the composition ratio of the target titanium alloy Ti80 to obtain an original powder with an average particle size of 85 μm. The original powder is transferred to a sealed quartz container and evacuated to 10 -3Pa, nitrogen protection was introduced, the distance between the ultraviolet light and the original powder was 1 cm, the container thickness was 0.5 cm, and ultraviolet light (power 300 W) was irradiated for 24 h for activation treatment;
[0066] (2) The activated powder in step (2) is pressed into a cylindrical billet by cold isostatic pressing at a pressure of 250 MPa and a holding time of 10 min.
[0067] (3) The temperature is raised to 900°C at a rate of 10°C / min and sintered for 0.5h to obtain a high-performance titanium alloy material.
[0068] Example 5
[0069] (1) The hydrogenated dehydrogenated titanium powder and the intermediate alloy powder required for preparing the target titanium alloy were mixed according to the composition ratio of the target titanium alloy Ti80 to obtain an original powder with an average particle size of 55 μm, which was transferred into a sealed quartz container and evacuated to 10 -3 After Pa, helium protection was introduced, the distance between the ultraviolet light and the original powder was 10 cm, the thickness of the container was 1.5 cm, and ultraviolet light (power 300 W) was irradiated for 24 hours for activation treatment;
[0070] (2) The activated powder in step (2) is pressed into a cylindrical billet by cold isostatic pressing at a pressure of 250 MPa and a holding time of 20 min.
[0071] (3) The temperature is raised to 990°C at a rate of 10°C / min and sintered for 1.9h to obtain a high-performance titanium alloy material.
[0072] Example 6
[0073] (1) The hydrogenated dehydrogenated titanium powder and the intermediate alloy powder required for preparing the target titanium alloy were mixed according to the composition ratio of the target titanium alloy Ti80 to obtain an original powder with an average particle size of 95 μm, which was transferred into a sealed quartz container and evacuated to 10 -3 After Pa, helium protection was introduced, the distance between the ultraviolet light and the original powder was 2 cm, the container thickness was 1 cm, and ultraviolet light (power 250 W) was irradiated for 22 h for activation treatment;
[0074] (2) The activated powder in step (2) is pressed into a cylindrical billet by cold isostatic pressing at a pressure of 250 MPa and a holding time of 20 min.
[0075] (3) The temperature is raised to 1000°C at a rate of 10°C / min and sintered for 2 h to obtain a high-performance titanium alloy material.
[0076] Example 7
[0077] (1) The hydrogenated dehydrogenated titanium powder and the intermediate alloy powder required for preparing the target titanium alloy were mixed according to the composition ratio of the target titanium alloy Ti80 to obtain the original powder with an average particle size of 100 μm, transferred to a sealed quartz container, and evacuated to 10 -3 After Pa, helium protection was introduced, the distance between the ultraviolet light and the original powder was 3 cm, the container thickness was 1 cm, and ultraviolet light (power 150 W) was irradiated for 24 h for activation treatment;
[0078] (2) The activated powder in step (2) is pressed into a cylindrical billet by cold isostatic pressing at a pressure of 250 MPa and a holding time of 20 min.
[0079] (3) The temperature is raised to 1050°C at a rate of 10°C / min and sintered for 2 h to obtain a high-performance titanium alloy material.
[0080] Example 8
[0081] (1) The hydrogenated dehydrogenated titanium powder and the intermediate alloy powder required for preparing the target titanium alloy were mixed according to the composition ratio of the target titanium alloy Ti80 to obtain the original powder with an average particle size of 140 μm, which was transferred into a sealed quartz container and evacuated to 10 -3 After Pa, helium protection was introduced, the distance between the ultraviolet light and the original powder was 1 cm, the thickness of the container was 1 cm, and ultraviolet light (power 100 W) was irradiated for 24 hours for activation treatment;
[0082] (2) The activated powder in step (2) is pressed into a cylindrical billet by cold isostatic pressing at a pressure of 250 MPa and a holding time of 20 min.
[0083] (3) The temperature is raised to 1050°C at a rate of 10°C / min and sintered for 0.5h to obtain a high-performance titanium alloy material.
[0084] Example 9
[0085] (1) The hydrogenated dehydrogenated titanium powder and the intermediate alloy powder required for preparing the target titanium alloy were mixed according to the composition ratio of the target titanium alloy Ti80 to obtain an original powder with an average particle size of 70 μm, which was transferred into a sealed quartz container and evacuated to 10 -3 After Pa, helium protection was introduced, the distance between the ultraviolet light and the original powder was 1 cm, the thickness of the container was 1 cm, and ultraviolet light (power 200 W) was irradiated for 24 hours for activation treatment;
[0086] (2) The activated powder in step (2) is pressed into a cylindrical billet by cold isostatic pressing at a pressure of 250 MPa and a holding time of 20 min.
[0087] (3) The temperature is raised to 1050°C at a rate of 10°C / min and sintered for 2 h to obtain a high-performance titanium alloy material.
[0088] Figure 2 3 is a SEM image of the titanium alloy powder activated by ultraviolet light in Example 1. It can be seen from the image that the surface state of the titanium alloy powder prepared in Example 1 has not changed. Figure 3 This is a crystal phase diagram of the titanium alloy prepared after activated sintering in Example 1. It can be seen from the picture that the titanium alloy prepared in Example 1 has a high density and there are basically no pores inside the grains. Figure 4 The middle curve (a) is the mechanical property curve of the titanium alloy prepared in Example 1, Figure 4 The middle curve (b) is the mechanical property curve of the titanium alloy prepared in comparative example 1. It can be seen from the picture that the mechanical properties of the titanium alloy prepared in Example 1 are good, with a tensile strength of 600 MPa and an elongation of 30%. However, the mechanical properties of the titanium alloy prepared in comparative example 1 are poor, with a tensile strength of only 430 MPa and an elongation of 23%, which is due to the large number of pores remaining inside the material, which seriously damages the performance of the material. Figure 5 This is the SEM image of the titanium alloy powder of Comparative Example 1. Figure 2 and Figure 5 It can be seen that the powder morphology has not changed significantly. Figure 6 This is the crystal phase diagram of the titanium alloy of comparative example 1. It can be seen from the picture that the density of the prepared titanium alloy is low and there are a large number of pores inside the grains.
[0089] The comparative experiment fully proves that the high-performance titanium alloy sintered by UV-assisted activation of the present invention has greatly improved mechanical properties and density while reducing the sintering temperature and shortening the sintering time. At the same time, the comparative experiment also found an unexpected increase in elongation. The elongation of the high-performance titanium alloy sintered by UV-assisted activation reached 30%, while the elongation of the titanium alloy directly sintered without UV-assisted activation was 23%.
[0090] In Example 2 and Example 1, the distance between the ultraviolet light and the original powder is 3 cm, and the thickness of the quartz container is 1 mm. In Example 1, the ultraviolet light is irradiated at different angles by rotating the container. In Example 2, the light-transmitting device is placed in a box with an ultraviolet light source. The box with an ultraviolet light source is usually a light source. Because the light is in all directions, the entire box looks like it has light. In this way, the ultraviolet light placed in the container can irradiate the powder from different angles. However, if the container is not rotated, the irradiation is still insufficient. Therefore, rotating the device can make the original powder be fully irradiated by ultraviolet light at different angles. Compared with Example 1, because the ultraviolet light irradiation is more sufficient and the activation effect is better, the temperature of Example 2 is lower than that of Example 1 during sintering.
[0091] Example 3 is pressed by molding, and Example 1 is pressed by cold isostatic pressing. Both methods can prepare high-performance titanium alloys.
[0092] In the traditional preparation method, when no ultraviolet light irradiation is performed, the sintering temperature is 1250°C and the sintering time is 4 hours. Ultraviolet light-assisted activation can reduce the sintering temperature and shorten the sintering time. In particular, under the conditions of "short distance between ultraviolet light and original powder, small container thickness, high ultraviolet light power, and long irradiation time" in Example 4 of the present invention, the sintering temperature is shortened by a maximum of 350°C and the sintering time is shortened by a maximum of 3.5 hours through ultraviolet light-assisted activation, which fully demonstrates that compared with the traditional method, the present invention can greatly reduce the sintering time and sintering temperature of titanium alloys, significantly reduce production costs, and has strong industrial application prospects.
[0093] By comparing Examples 4 and 5, it can be seen that when the distance between the ultraviolet light and the original powder increases and the thickness of the container increases, the sintering temperature and sintering time need to be increased accordingly to ensure that the prepared product is a high-performance titanium alloy.
[0094] By comparing Example 6 with Example 4, it can be found that when the distance between the ultraviolet light and the original powder increases, the thickness of the container increases, the ultraviolet light power decreases, and the irradiation time shortens, at this time, in order to ensure product performance, the sintering temperature increases, and the sintering time increases. However, in summary, after ultraviolet light assisted activation, the sintering temperature is still lower than that of the traditional technology, and the sintering time is still shorter than that of the traditional technology.
[0095] By comparing Examples 7-9, it can be seen that when the power of ultraviolet light is between 100W-200W, the irradiation time should be increased, the distance between the ultraviolet light and the original powder should be shortened as much as possible, the sintering temperature should be appropriately increased, and the sintering time should be increased, so that the product prepared by ultraviolet light assisted activation can be a high-performance titanium alloy.
[0096] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for sintering titanium alloy by ultraviolet light assisted activation, characterized in that: The steps include: (1) mixing the hydrogenated dehydrogenated titanium powder and the intermediate alloy powder required for preparing the target titanium alloy according to the target titanium alloy component ratio to obtain an original powder; (2) Use ultraviolet light to irradiate the original powder from different angles for activation treatment, wherein the distance between the ultraviolet light and the original powder is 1 cm-3 cm, the power of the ultraviolet light is 200 W-300 W, and the irradiation time is 20 h-24 h to obtain the activated powder, and the activated powder is pressed into a billet, and the billet is sintered at a sintering temperature of 900°C-1000°C and a sintering time of 0.5 h-2 h to obtain a titanium alloy for preparing large-sized titanium alloy structural parts with a mass greater than 1 kg.
2. A method for sintering titanium alloy by ultraviolet light assisted activation as claimed in claim 1, characterized in that: The activation treatment is achieved by: The original powder is placed in a light-transmitting device, and while the light-transmitting device is rotated, ultraviolet light is used to irradiate the original powder from the outside of the light-transmitting device to perform activation treatment.
3. The method for sintering titanium alloy by ultraviolet light assisted activation according to claim 1, characterized in that: The activation treatment is achieved by: After the original powder is placed in the light-transmitting device, the light-transmitting device is placed in a box with an ultraviolet light source. While the light-transmitting device is rotated, the ultraviolet light in the box irradiates the original powder from different angles to perform activation treatment.
4. A method for sintering titanium alloy by ultraviolet light assisted activation as claimed in claim 2 or 3, characterized in that: The light-transmitting device is a sealed container. Before the original powder is irradiated with ultraviolet light, the original powder is placed in the light-transmitting device, which is first evacuated and then protected by an inert gas.
5. A method for sintering titanium alloy by ultraviolet light assisted activation as claimed in claim 2 or 3, characterized in that: The light-transmitting device is a quartz container with a thickness of 0.5 mm to 1.5 mm, and the particle size of the original powder is less than or equal to 150 μm.
6. A titanium alloy sintered by ultraviolet light assisted activation, characterized in that: The titanium alloy is prepared by a method for sintering a titanium alloy by ultraviolet light assisted activation as described in any one of claims 1 to 5.
7. An application of titanium alloy sintered by ultraviolet light assisted activation, characterized in that: The titanium alloy is prepared by a method for sintering a titanium alloy by ultraviolet light-assisted activation as described in any one of claims 1 to 5, and the titanium alloy is used to prepare large-sized titanium alloy structural parts with a mass greater than 1 kg.
Citation Information
Patent Citations
Method for preparing high-performance powder metallurgy titanium and titanium alloy from superfine titanium powder
CN112941366A
Functionalized metal powders by small particles made by non-thermal plasma glow discharge for additive manufacturing applications
CN113966256A